Aripiprazole-induced liver injury: a spontaneous reporting database study - Gao, Yunjuan; Wu, Chengzhao; Zhai, Xingran; Niu, Ming; Bai, Zhaofang; Song, Haibo; Zhao, Xu; Wang, Jiabo; Xiao, Xiaohe (Frontiers in Pharmacology, 2023)
Background: There have been individual case reports of aripiprazole in recent years, both domestically and internationally, but no analysis of the characteristics of the occurrence of adverse reactions/events of drug-induced liver injury with aripiprazole using spontaneous reports has been seen. Methods: Using a retrospective study approach, the 452 adverse reaction/event reports of aripiprazole-induced liver injury collected by the China Adverse Drug Reaction Monitoring System from 1 January 2012 to 31 December 2016 were analyzed and evaluated, and exploring it’s the clinical characteristics and related risk factors for liver injury occurrence. Results: Among 452 cases of aripiprazole-induced liver injury ADR/ADE reports, there were 121 cases classified as serious, accounting for 26.8% of the total. There were 250 male and 202 female patients, with a male-to-female ratio of 1.24:1. The age of patients ranged from 11 to 77 years old, with an average age of (34.56 ± 12.81) years old, and a high proportion of young adults in the total population. Some patients had used the drug off-label or at a higher than recommended dosage. The onset of liver injury was generally within 15–90 days after continuous use, while some patients are also accompanied by nausea, vomiting, and weight gain. 70% of the combined drug instructions listed that may cause liver injury. Conclusion: In clinical practice, healthcare professionals should pay closely attention to the adverse reactions and risk factors of liver injury caused by aripiprazole. If there are potential risk factors for liver injury, early and regular monitoring of liver function should be carried out to reduce the occurrence of adverse reactions.